Low energy availability interferes with exercise-associated bone effects in female long-distance triathletes as detected by HR-pQCT - Gama, E. M. F.; Kasuki, L.; Paranhos-Neto, F. P.; Madeira, M.; Mendonça, L. M. C.; Schtscherbyna, A.; Farias, M. L. F. (Journal of Clinical Densitometry, 2022)
Female Athlete Triad, initially described as the association of disordered eating, amenorrhea and osteoporosis, was further redefined to focus on low energy availability (EA), which has a central role in development of hypoestrogenism and low bone mineral density (BMD). However, the contribution of each variable, that is, low EA and hypoestrogenism, for bone derangements is still an open question. To evaluate body composition and bone status in long-distance triathletes without hypoestrogenism, as compared to non-athletes, using DXA and HR-pQCT, and the influence of EA. Population comprised 23 triathletes who had completed at least one long-distance race in the previous year, and 17 non-athletic healthy controls. The athletes denied previous oligo-amenorrhea and had spontaneous regular menses or were on hormonal contraceptives. Control patients also had regular menses. Energy deficiency (low EA) was defined as energy intake below the recommended level for athletes, that is, 45 kcal/kg free fat mass/day. Only femoral neck BMD Z-score measured by DXA trended higher in athletes (p=0.05), whereas high-resolution peripheral quantitative computed tomography detected significantly higher values of entire bone and trabecular bone area, cortical perimeter, trabecular vBMD and trabecular bone volume/tissue volume, and lower trabecular separation and trabecular inhomogeneity in athletes. No difference was found between athletes with spontaneous menses and those on hormone contraceptives in respect to all parameters. The effects of exercise on bone were not so pronounced in athletes with low EA, although they still had better bone parameters than controls. Stress fractures were reported by 4:12 athletes with low EA and by 2:11 athletes with adequate EA. Long-distance female triathletes without hypoestrogenism show higher values of cortical perimeter, bone area, volumetric density and trabecular microstructure, but low EA interferes with exercise-associated bone effects. These innovative findings reinforce the importance of adequate EA in female athletes to guarantee skeletal health.